REGIONAL FEATURES OF MIGRATION IN THE NORTH CAUCASUS IN 1920-1930-S - Ivan Alekseyevich Soloviev (Наука. Инновации. Технологии)
The study revealed the intensity of migration mobility of the population of the arrival of the North Caucasus in the 1920-s. and the analysis of the dynamics of migration growth of the urban population of the North Caucasus in the late 1920-s - early 1940-s. Considered sexual features of migration mobility, as well as the difference between this indicator between rural and urban areas of the North Caucasus. In the article the regional characteristics of migratory relations in the North Caucasus with the subjects of the Russian Federation and the republics of the USSR, as well as identified the territorial structure of the migration turnover. The paper identified the impact of the migration of urban population Ordzhonikidze Territory and regional features of migration growth of the province in 1940.